2017
DOI: 10.1021/acsami.7b07769
|View full text |Cite
|
Sign up to set email alerts
|

Potency and Cytotoxicity of a Novel Gallium-Containing Mesoporous Bioactive Glass/Chitosan Composite Scaffold as Hemostatic Agents

Abstract: Chitosan-based hemostats are promising candidates for immediate hemorrhage control. However, they have some disadvantages and require further improvement to achieve the desired hemostatic efficiency. Here, a series of 1% GaO-containing mesoporous bioactive glass-chitosan composite scaffolds (Ga-MBG/CHT) were constructed by the lyophilization process and the effect of various concentrations of Ga-MBG (10, 30, and 50 wt %) on the hemostatic function of the CHT scaffold was assessed as compared to that of Celox R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 52 publications
5
55
0
Order By: Relevance
“…On the basis, Ga-MBG/CS composite scaffolds containing various concentrations of Ga-MBG were constructed using the lyophilization method and their properties and hemostatic efficacy were assessed [31]. The results demonstrated that Ga-MBG/CS scaffolds with high porosity exhibited increased water uptake compared to that of commercially available Celox rapid gauze (CXR).…”
Section: Cs-based Composite Hemostatic Materialsmentioning
confidence: 99%
“…On the basis, Ga-MBG/CS composite scaffolds containing various concentrations of Ga-MBG were constructed using the lyophilization method and their properties and hemostatic efficacy were assessed [31]. The results demonstrated that Ga-MBG/CS scaffolds with high porosity exhibited increased water uptake compared to that of commercially available Celox rapid gauze (CXR).…”
Section: Cs-based Composite Hemostatic Materialsmentioning
confidence: 99%
“…So, the clotting ability of acetate chitosan and acetate chitosan/CaCO 3 hydrogels was assessed by determining absorbance of the supernatant of the nonclotted blood at 540 nm. The lower absorbance reflects less hemoglobin in the sample and therefore indicated a higher coagulation rate . As shown in Figure , the absorbance of acetate chitosan/CaCO 3 hydrogels was much lower than that of single acetate chitosan hydrogels.…”
Section: Resultsmentioning
confidence: 93%
“…The lower absorbance reflects less hemoglobin in the sample and therefore indicated a higher coagulation rate. 39 As shown in Figure 8, the absorbance of acetate chitosan/CaCO 3 hydrogels was much lower than that of single acetate chitosan hydrogels. The results indicated that the acetate chitosan/ CaCO 3 hydrogels exhibited a higher clotting ability.…”
Section: Whole Blood Clotting Testsmentioning
confidence: 88%
“…Quana et al (2015) proved that ultrafast absorption of cross‐linked graphene sheets provided rapid hemostasis. In another study, Pourshahrestani et al (2017) displayed comparatively decreased absorption and superior hemostatic performances while increasing the percentage of gallium in bioglass network. Similarly, in our case, 800‐3h absorption rate is less compared with 550‐3h, as it showed acceptable hemostatic behavior that was further confirmed by thrombus formation assay.…”
Section: Discussionmentioning
confidence: 94%
“…According to previously reported explanations, it is understood that the material which could be able to release higher Ca 2+ and subsequent interaction with blood can arrest the functions and generates clot. Ca 2+ ions contribution to activate intrinsic pathway is phenomenal, but it also plays the role toward the acceleration of thrombin shadowed by fibrin (Dai et al, 2009; Pourshahrestani et al, 2017).…”
Section: Discussionmentioning
confidence: 99%